Three new species and a new combination in the genus Omaliopsis Jeannel, 1940 (Coleoptera: Staphylinidae: Omaliinae: Omaliini) of China and Nepal - Shavrin, Alexey V. (Zootaxa, 2019)
Three new species of the genus Omaliopsis Jeannel, 1940 from East Asia are described: O. amplimaculata sp.n. (China: Sichuan, Emei Shan), O. bimaculata sp.n. (China: Yunnan, Xue Shan and Haba Shan) and O. schmidti sp.n. (central Nepal). A new combination is proposed for Chinese O. musaphila (Rougemont, 2017) comb. n., originally described in the genus Phyllodrepa Thomson, 1859. A key for species of Omaliopsis known from East Asia is proposed. Members of the genus Omaliopsis are recorded for the first time from China and Nepal.